FarMoRe provides an inclusive digital solution to co-create agroecology at scale for rice production in Vietnam - Nelson, Katherine; Bui Tan Yen; Vu Hong Trang; Ong Quoc Cuong; Nguyen Bao Tran (International Rice Research Institute, 2024)
This policy brief introduces FarMoRe - a field-level performance assessment app that fosters co-creation and collaboration between extension agents and farmers. By enabling users to record, benchmark, and monitor farming practices over time, FarMoRe serves as a tool for advancing agroecology in Vietnam. The social benchmarking feature of FarMoRe allows users to compare their performance metrics against those of peers, promoting a sense of accountability and motivating individuals to align their actions with perceived norms. Aligned with Vietnam’s national sustainability policies, FarMoRe supports agroecological transitions by enhancing traceability and promoting reduced chemical inputs and green growth. The FarMoRe case study exemplifies how digital solutions can contribute to building resilient and low-emission agricultural systems.